Comparative study of accelerated carbonation of plain cement and fly-ash concrete. (March 2017) - Hussain, Shaik; Bhunia, Dipendu; Singh, S.B.
Abstract: Accelerated carbonation of plain cement concrete and concrete with fly-ash replacing cement partially, is discussed in the present paper. Mechanical properties such as compressive strength, flexural strength, modulus of elasticity, durability aspects such as depth of carbonation and porosity of carbonated concrete are studied. To study the influence of water binder ratio on the above-mentioned properties, water-binder ratios of 0.35, 0.50 and 0.65 are used. It is observed that the mechanical properties of carbonated concrete have increased with the duration of carbon dioxide exposure. So did the depth of carbonation, whereas the volume of permeable voids has reduced leading to the decrease in porosity. An expression to predict the depth of carbonation of fly-ash concrete has also been developed. Highlights: Carbonation depth of fly ash blended cement concrete is proposed. The dependency of square root t law for the ingress of carbon dioxide into concrete is checked. Effect of water-binder ratio on carbonation depth of OPC and fly ash concrete is studied.